THE EFFECTS LEARNING MEDIA AND VOCABULARY MASTERY TOWARDS DESCRIPTIVE TEXT SKILL - Munap Munap; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2019)
This research aims to get information and test the hypothesis of the effects of learning media and vocabulary mastery towards the descriptive writing skill at state junior high school in Serang. The research hypothesis is 1) there is no effect of learning media on the descriptive writing skill at state junior high school in Serang. 2) there is any effect of vocabulary mastery towards the descriptive writing skill at state junior high school in Serang. 3) There are any interactive effects of learning media and vocabulary mastery towards the students’ descriptive writing skills. This research method uses an experiment with a 2 x 2 factorial design. Using a random sampling technique, the interpretation sample established 60 students of two classes in grade 8 at state junior high school in Serang by giving 40 items for vocabulary items and one item for writing text. The results conclude that first, there are learning media effects towards descriptive writing skills at state junior high school in Serang. It is proved the analysis of data obtained Fo = 5,975, and Sig = 0,018<0,05. Second, Vocabulary Mastery has effects on the descriptive writing skill at state junior high school in Serang. It is proved the analysis of data obtained Fo = 7,955. and Sig = 0,007<0.05. Third, there are interactive effects of learning media and vocabulary mastery towards the students’ descriptive writing skills. It is based on the analysis of interaction data Fo = 12,763, and Sig = 0,001< 0,05. This research concluded that writing descriptive text skills could be achieved by increasing vocabulary mastery and using learning media.